Pengabdian kepada Masyarakat melalui Kuliah Kerja Nyata (KKN) di Kelurahan Bambu Kuning Pekanbaru - Fithri, Radhiyatul; Mudzakki, Muhammad Fahmil; Patira, Mozza; Ayu, Liska; Naibaho, Ratna (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Community service through Community Service Programs (KKN) is one way students contribute to addressing community issues. This study aims to examine the role of KKN in increasing environmental awareness and providing education to children in Bambu Kuning Village, Pekanbaru City. The method used in this study was observation. KKN students participated in environmental cleanup activities, provided counseling on the importance of maintaining cleanliness, and provided education to children about the importance of protecting the environment. The results showed that through KKN, environmental awareness in Bambu Kuning Village experienced a significant increase. The community began to understand the importance of maintaining cleanliness and caring for their surroundings. Children also showed increased knowledge about the importance of protecting the environment through educational activities carried out by KKN students.